ANALYSIS OF THE EFFECT AMOUNT OF PLATE, DIAMETER PORT, AND WIDTH OF COMPRESSION ON INTERCOOLER PERFORMANCE IN PT INDONESIA POWER - Elli Prastyo (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2020)
This analysis to determine the performance of the intercooler based on actual data, and the intercooler's performance against design specifications changes using the NTU method. Variable design specifications in the study are the number of plates, compressed area, and port diameter values from intercooler specifications provided by the company. The results of the inter-device performance analysis of compatibility with the specifications required by the company amounted to 99.40%. The results of the first trial of the tool specifications point the compatibility value to increase to 99.98% by increasing the number of plates from 79 to 150 plates, reducing the compressed area value from 0.47 to 0.2 m and increasing the port diameter value from 0.2 to 0,5 m. The results of the trial 2 tool specification showed a decrease to 86.51% due to changes in variable variables, by the number of plates to 25, raising the compressed plate width to 0.5 meters and increasing the port diameter to 0.6 m. The highest overall heat transfer value on May 23-24 is 346.225,37 Â based on actual data calculation of Intercooler effectiveness. The lowest overall heat transfer value is 346.213,29 Â based on data calculation it occurred on 22 May 2019.